Endothelin-1 and nitric oxide in 3-year prognosis after acute myocardial infarction - Apostolović, Svetlana; Salinger-Martinović, Sonja; Janković-Tomašević, Ruzica; Djordjević-Radojković, Danijela; Pavlović, Milan; Kostić, Tomislav; Cosić, Vladan; Ristić, Tatjana; Stojanović, Ivana (Vojnosanitetski pregled, 2017)
Background/Aim. Acute myocardial infarction (AMI) is an important cause of mortality/morbidity worldwide. Biomarkers improve diagnostic and prognostic accuracy in AMI. The aim of this study was to investigate an increase of markers of endothelial dysfunction in AMI, measured on the 3rd day after the initial event and to investigate their association with short- and long-term (3-year) prognosis (outcome). Methods. The prospective study included 108 patients with AMI in the experimental group and 50 apparently healthy subjects in the control group. Endothelin-1 (ET-1) and nitric oxide degradation products (NOx) were determined. Results. The average age of the participants in the experimental group was 62 ± 10 years and 59 ± 9 years in the control group; 74.1% of the patients in experimental group were males and 68.8% in the control group. In 74.1% of the patients, ST-elevation myocardial infarction (STEMI) was diagnosed, and 25.9% of the patients presented with non-ST-elevation myocardial infarction (NSTEMI). Thirteen (5.6%) patients died during 3 years and they had significantly higher ET-1 levels compared to survivors [4.02 (2.72–5.93) vs 3.06 (2.23–3.58) pg/mL; p = 0.015]. Endothelin-1 in 46 (42.6%) patients with composite endpoint (3-year mortality and rehospitalization) was significantly increased compared to other patients [3.14 (2.54–4.41) vs 3.05 (2.18–3.56) pg/mL; p = 0.035]. Intrahospital complications were found in 41 (48%) patients. Participants with echocardiographically detected complications (ventricular dyskinesia, left ventricular thrombus and papillary muscle rupture) had higher ET-1 levels compared to other patients [4.02 (2.78–5.57) vs 3.06 (2.29–3.66) pg/mL; p = 0.012]. Endothelin-1 concentration above the 75th percentile (> 3.77 pg/mL) was associated with the increased risk for composite endpoint [Log Rank (χ2 = 13.44; p 3.77 pg/mL) was associated with the increased risk for composite endpoint [Log Rank (χ2=13.44, p
Keywords: myocardial infarction; biological markers; ultrasonography; endothelins; nitric oxide; prognosis; sensitivity and specificity